Socio-Economic Status and Social Capital: A Multicausal Analysis of Bullying Among Highschool Students in Karawang, West Jawa - Wicaksono, Hendri (UI Scholars Hub, 2019)
The high number of bullying cases among students is one of the problems of education in Indonesia. Previous studies stated that socio economic status (SES), social capital, ethnicity and parenting were the factors leading to the practice of bullying in schools. Students with low SES levels more often fall victim to bullying compared to students who have high SES levels. Likewise, with social capital, students who have a low level of popularity and weak social networks are more vulnerable of bullying from their friends.In addition, victims of bullying are often students from ethnic minorities. Students who become victims of bullying also tend to have strict and overprotective parents. By using a quantitative approach in the form of a survey and binary logistic regression data processing technique, in this article the author uses two main variables, namely SES and social capital, which is then analysed using multicausal analysis simultaneously to observe the more dominant factors in influencing the practice of bullying at school. The results show that students who have low social capital are six times more likely to be victims than students who have high social capital.Meanwhile, the SES level variable is stated not to correlate with bullying in SMAN X in Karawang, West Java. Therefore, the variable of social capital is known to be a more dominant factor as a causeof the practice of bullying compared to the variable of SES level.